PENGARUH PROFITABILITAS, LEVERAGE DAN KEPUTUSAN INVESTASI TERHADAP NILAI PERUSAHAAN (STUDI EMPIRIS PERUSAHAAN PERTAMBANGAN DI BURSA EFEK INDONESIA TAHUN 2015-2018) - Komala Dewi; Hari Sulistiyo (Departemen Manajemen, 2020)
This study aims to determine whether there is an influence between profitability, leverage and investment decisions on firm value. The research method used is descriptive and verification, where descriptive using descriptive statistics and multiple linear regression analysis was used for verification with the help of SPSS 24 software. The research samples taken were 9 companies from a total of 38 mining companies listed on the Indonesia Stock Exchange in 2015-2018 with the sampling technique used was purposive sampling. The results show profitability has effect on firm value, leverage has not effect on firm value and investment decisions has effect on firm value. Whereas for simultaneous testing, the results show profitability, leverage and investment decisions simultaneously has an effect on firm value. Therefore, companies and investors need to pay attention to the level of profitability and investment decisions because these two variables can increase the firm value.